2022
DOI: 10.3389/fphar.2022.949713
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA-related CeRNA network and prognostic signature for patients with oral squamous cell carcinoma

Abstract: Background: Circular RNA (circRNA) has an important influence on oral squamous cell carcinoma (OSCC) progression as competing endogenous RNAs (ceRNAs). However, the link between ceRNAs and the OSCC immune microenvironment is unknown. The research aimed to find circRNAs implicated in OSCC carcinogenesis and progression and build a circRNA-based ceRNA network to create a reliable OSCC risk prediction model.Methods: The expression profiles of circRNA in OSCC tumors and normal tissues were assessed through RNA seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
2
1
0
Order By: Relevance
“…Previous studies have shown that cellular senescence and senescence‐associated cytokines are major modulators in head and neck squamous cell carcinoma development 59,60 . He et al found circRNAs implicated in OSCC carcinogenesis and progression through RNA sequencing and assessed differentially expressed circRNAs by GO and KEGG analysis 61 . In their study, genes were mainly enriched in cellular senescence, which was consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown that cellular senescence and senescence‐associated cytokines are major modulators in head and neck squamous cell carcinoma development 59,60 . He et al found circRNAs implicated in OSCC carcinogenesis and progression through RNA sequencing and assessed differentially expressed circRNAs by GO and KEGG analysis 61 . In their study, genes were mainly enriched in cellular senescence, which was consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“… 59 , 60 He et al found circRNAs implicated in OSCC carcinogenesis and progression through RNA sequencing and assessed differentially expressed circRNAs by GO and KEGG analysis. 61 In their study, genes were mainly enriched in cellular senescence, which was consistent with our results. Moreover, homologous recombination is known as a DNA repair pathway of clinical interest in cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, in 2011, Salmena et al proposed the ceRNA hypothesis 8 , which has attracted widespread attention from researchers and stated that coding and ncRNA molecules with common MREs can compete for miRNA binding at these loci and thus indirectly reciprocally regulate expression by acting as miRNA sponges 9 . CircRNAs are a novel class of noncoding ceRNAs and have a circular structure formed by the covalent closure of precursor messenger RNAs (pre-mRNAs) through backsplicing 10 . CircRNAs have no 5′ cap or 3′ tail and are thus not easily degraded by ribonucleases.…”
Section: Introductionmentioning
confidence: 99%